PREDICTION OF SUCCESS IN TEACHER TRAINING - Burns, Mildred (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1977)
Two of the most pressing questions regarding preparation of teachers continue to be how success in teaching can be predicted, and what the teacher training program should consist of. The following study attempts to look at some aspects of these two questions by an analysis of data available for 35 teacher interns in the MEET Project of McGill University.